2007
DOI: 10.1099/mic.0.2006/003467-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional studies of intimin in vivo and ex vivo: implications for host specificity and tissue tropism

Abstract: Intimin is an outer-membrane adhesin that is essential for colonization of the host gastrointestinal tract by attaching and effacing pathogens including enteropathogenic Escherichia coli (EPEC), enterohaemorrhagic E. coli (EHEC) and Citrobacter rodentium (CR). The N-terminus of intimin from the different strains is highly conserved while the C-terminus, which harnesses the active receptor-binding site, shows sequence and antigenic polymorphism. This diversity was used to define a number of distinct intimin typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Phillips and coworkers have established an IVOC from pediatric biopsy specimens of duodenum mounted in a modified MicroSnapwell system specifically adapted for use with 2-to 3-mmdiameter biopsy samples. This IVOC system has been used mainly to study the mechanisms of virulence of ETEC (839), EPEC (840)(841)(842)(843)(844)(845)(846)(847)(848)(849)(850)(851), EHEC (852)(853)(854)(855)(856)(857), EAEC (507,858), and Salmonella (392) and the action of Stx toxins (641). Other IVOCs have been used for studies on C. jejuni (859), EPEC (692,860,861), EAEC (645,(862)(863)(864), and Shigella (865) pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Phillips and coworkers have established an IVOC from pediatric biopsy specimens of duodenum mounted in a modified MicroSnapwell system specifically adapted for use with 2-to 3-mmdiameter biopsy samples. This IVOC system has been used mainly to study the mechanisms of virulence of ETEC (839), EPEC (840)(841)(842)(843)(844)(845)(846)(847)(848)(849)(850)(851), EHEC (852)(853)(854)(855)(856)(857), EAEC (507,858), and Salmonella (392) and the action of Stx toxins (641). Other IVOCs have been used for studies on C. jejuni (859), EPEC (692,860,861), EAEC (645,(862)(863)(864), and Shigella (865) pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous EHEC genes have been shown to be important for adherence of this pathogen to tissue culture monolayers (60) and animal intestinal explants (34,48) and to promote persistence in ruminant reservoir hosts (10,11); however, with the exception of proteins encoded in the LEE pathogenicity island (9,43,44), the roles of candidate adhesion factors in animal models of disease are not known. Here, we identified three EHEC genes (adfO [Z2053], located on prophage CP-933O; yodA, a gene also found in E. coli K-12; and etpC, a gene located on pO157) that contribute to adherence of EHEC to HeLa cell monolayers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the variability in sample properties between donors and results is far greater than in cell line models. The IVOC system has been used to study EPEC-host specificity and tissue tropism (Girard et al 2005;Mundy et al 2007), Tir-intimin-dependent colonization and A/E lesion formation (Frankel et al 1998a;Schüller et al 2007;Frankel and Phillips 2008). The polarized IVOC method has shown that apical EPEC infection of duodenal mucosa results in a flagellin-dependent increase in IL-8 levels (Schüller et al 2009).…”
Section: In Vitro Infection Modelsmentioning
confidence: 99%